If the roots of the equation (b-c)x2 +(c-a)x +(a-b) = 0 are equal than prove that

2b = c + a

Dear Student!

**@kapil :** Your friend has provided you correct answer! Hope you got it!

**@pankaj : **Good Work! Keepit up & Keep Posting!

Cheers!

**
**

If the roots of the equation (b-c)x2 +(c-a)x +(a-b) = 0 are equal than prove that

2b = c + a

Dear Student!

**@kapil :** Your friend has provided you correct answer! Hope you got it!

**@pankaj : **Good Work! Keepit up & Keep Posting!

Cheers!

**
**

What are you looking for?